Faktor Keputusan Pembelian Thrift Shopping Pada Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Jakarta - Indriani, Aisah; Purwandari, Dian Alfia; Saipiatuddin, Saipiatuddin (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2023)
This study aims to determine the effects of conformity on thrift shopping purchase decisions among students of the Faculty of Social Sciences, Jakarta State University. This research uses a quantitative method with purposive sampling technique. The research was conducted with the condition that the respondents are thrift shopping consumers and active students of the Faculty of Social Sciences, Jakarta State University. The sample obtained was 95 students out of a population of 125 students. Based on the t-test results, the calculated t-value of 4.928 is greater than the t-table value of 1.989, which means there is an influence of conformity on thrift shopping purchase decisions among students of the Faculty of Social Sciences, Jakarta State University, with a low level of influence. Abstract Penelitian ini bertujuan untuk mengetahui pengaruh konformitas terhadap keputusan pembelian thrift shopping pada mahasiswa Fakultas Ilmu Sosial Universitas Negeri Jakarta. Penelitian ini menggunakan metode kuantitatif dengan teknik pengambilan sampel purposive sampling. Penelitian dilakukan dengan syarat responden adalah konsumen thrift shopping dan mahasiswa aktif Fakultas Ilmu Sosial Universitas Negeri Jakarta. Sampel diperoleh berjumlah 95 mahasiswa dari jumlah populasi 125 mahasiswa. Berdasarkan Ujit, diperoleh hasil thitung = 4,928, lebih besar dari t tabel = 1,989, artinya terdapat pengaruh antara konformitas terhadap keputusan pembelian thrift shopping pada mahasiswa Fakultas Ilmu Sosial Universitas Negeri Jakarta dengan besaran pengaruh konformitas terhadap keputusan pembelian termasuk dalam kategori rendah.